Effect of fruit load on oil yield components and dynamics of fruit growth and oil accumulation in olive (Olea europaea L.) - Trentacoste, Eduardo Rafael (2010)
Olive oil yield and its components (fruit number, average fruit weight and fruit oil concentration) depend on crop load and source–sink ratios as affected by environmental conditions, management and the alternate bearing typical of the species. The aims of this work were to: (i) establish quantitative relationships between oil yield and its components as affected by fruit load in a high-yielding production system, (ii) analyse the dynamics of fruit weight and fruit oil concentration in terms of rates and durations, and (iii) explore the relationships between the dynamics of oil and water in fruit. In a fully irrigated olive orchard in Mendoza (32° S), Argentina, cv. Arbequina trees with similar crown volume and three fruit loads (3-fold range) were monitored during two seasons. Oil yield was positively associated with both fruit number and fruit fresh weight, but not with fruit oil concentration. Across seasons and fruit loads, fruit yield increased linearly with fruit number at ∼1.5 kg per thousand fruit and reached a maximum ∼60 kg tree−1 (or 25 t ha−1) at a fruit load of 32,700 fruit tree−1. The fruit filling rate was affected by fruit load, while the duration of fruit growth and the dynamics of oil and water concentration were unaffected by fruit load. Fruit water concentration reached a minimum at the onset of Stage III of fruit growth, which was marked by a rapid increase in oil concentration. Fruit fresh weight and oil weight increased with source–sink ratio from ∼0.5 up to a threshold ∼2 m3 crown per thousand fruit. In contrast, a 8-fold range of source–sink ratio did not affect fruit oil concentration.